Long-term management of gemcitabine in a patient with advanced pancreatic cancer undergoing haemodialysis. (December 2014) - Takakura, Kazuki; Koido, Shigeo; Takahara, Akitaka; Odahara, Shunichi; Mitobe, Jimi; Matsudaira, Hiroshi; Tsukinaga, Shintaro; Yukawa, Toyokazu; Matsumoto, Kei; Nagatsuma, Keisuke; Uchiyama, Kan; Kajihara, Mikio; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Gemcitabine application for patients with impaired renal function or undergoing haemodialysis will increase if the efficacy and safety are proved as the treatment for pancreatic cancer of these patients. However, there is no guideline about the usage of gemcitabine in patients with impaired renal function or haemodialysis. We report the case of a 70-year-old man with advanced pancreatic cancer undergoing haemodialysis. After discontinuation of 100% or 80% dosage, 60% dose of gemcitabine was administered biweekly. Serum carbohydrate antigen 19-9 and carcinoembryonic antigen levels were marked by slight variations and abdominal computed tomography (CT) showed the tumour size hardly changed. We administered gemcitabine for the patient 14 times in total, and he survived over 8 months from the definitive diagnosis. These findings confirm the efficacy and safety of treatment with a biweekly 60% dose of gemcitabine for patients with advanced pancreatic cancer undergoing haemodialysis in the face of dose modification.